Analisis Dampak Endorsment Selebriti Terhadap Minat Beli Skincare Pada Mahasiswa Manajemen Universitas Negeri Medan (UNIMED) - Agustina Nainggolan; Maya Martiza Sari; Anita Br Saragih; Imamul Khaira; Zulkarnain Siregar (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to determine the effect of Celebrity Endorsement on Skincare Purchase Intention in Management Students of Medan State University (Unimed). The subjects of this study were 30 management students of Medan State University (Unimed). The analysis prerequisite test includes normality test, linearity test and R test. The data analysis technique used is simple linear regression analysis. The results showed that there is a positive and significant relationship between celebrity endorsement and purchase intention.